The Impact of Emerging E-Commerce Platforms on Amazon’s Stock Price Performance - Matsepe, Nthabiseng; Fabian Moodley; Ferreira-Schenk, Sune (Acta Universitatis Danubius. Œconomica, 2025)
Objective: This study analyzes how emerging e-commerce competitors—Temu, eBay, and Etsy—influenced Amazon’s stock returns and volatility between 2018 and 2024. Approach: Using covariance analysis and GARCH-type models, the findings reveal that Amazon’s returns were significantly affected by market shocks and competitive pressures, with clear evidence of volatility clustering and asymmetric effects. While eBay and Etsy moved largely in tandem with Amazon, Temu’s returns displayed an inverse relationship, suggesting its rapid market expansion occurred partly at Amazon’s expense. Results: These results support the study’s objective by demonstrating that rising competition from new entrants materially altered investor sentiment and short-term stock performance in the global e-commerce space. The study also contributes to the intersection of the Efficient Market Hypothesis (EMH) and Behavioral Finance. It shows that investor reactions to competitive developments were not always rational, with herding behaviour and sentiment-driven responses amplifying short-term volatility. Amazon’s heightened sensitivity to firm-specific shocks, relative to broader market trends, underscores its exposure to competitive and innovation-driven risks in a fast-evolving digital landscape. Value: From a practical standpoint, the research highlights the importance for investors to monitor behavioural signals and market narratives, which can influence valuation and risk beyond traditional fundamentals. For e-commerce firms, the results underscore the need for continuous innovation, strategic differentiation, and adaptive pricing to retain market share. While limited by a focused sample and geographic scope, this study lays groundwork for future research incorporating broader datasets, cross-country analysis, and sentiment indices to better understand the interplay of competition and investor psychology in digital markets.